Lipid Nanoparticles for Drug Delivery. Issue 2 (25th November 2021) - Xu, Letao; Wang, Xing; Liu, Yun; Yang, Guangze; Falconer, Robert J.; Zhao, Chun-Xia
Abstract : Lipid nanoparticles have attracted significant interests in the last two decades, and have achieved tremendous clinical success since the first clinical approval of Doxil in 1995. At the same time, lipid nanoparticles have also demonstrated enormous potential in delivering nucleic acid drugs as evidenced by the approval of two RNA therapies and mRNA COVID‐19 vaccines. In this review, an overview on different classes of lipid nanoparticles, including liposomes, solid lipid nanoparticles, and nanostructured lipid carriers, is first provided, followed by the introduction of their preparation methods. Then the characterizations of lipid nanoparticles are briefly reviewed and their applications in encapsulating and delivering hydrophobic drugs, hydrophilic drugs, and RNAs are highlighted. Finally, various applications of lipid nanoparticles for overcoming different delivery challenges, including crossing the blood–brain barrier, targeted delivery, and various routes of administration, are summarized. Lipid nanoparticles as drug delivery systems offer many attractive benefits such as great biocompatibility, ease of preparation, feasibility of scale‐up, nontoxicity, and targeted delivery, while current challenges in drug delivery warrant future studies about structure–function correlations, large‐scale production, and targeted delivery to realize the full potential of lipid nanoparticles for wider clinical and pharmaceutical applications in future. Abstract : This article reviews the classification of different lipid nanoparticles, and their preparation and characterization. Their applications in encapsulating and delivering hydrophobic drugs, hydrophilic drugs, and RNAs for different diseases and how lipid nanoparticles enable nanomedicine to address the challenges of blood–brain barrier, targeted delivery, and various routes of administration are also discussed .